Risk Analysis in the Oil and Gas Industry by using SPSS (Study Field in the Project of Increasing Liquid Gas Storage in Iraq) - Obayes, Kadhim J. (Journal of Petroleum Research and Studies, 2025)
The oil and gas industry of Iraq is one of the largest industries in the country and provides a lot of income for the country. Because this industry is associated with many risks, risk analysis in this industry is very vital. Therefore, the present research was carried out in order to manage risk in the oil and gas industry in the project of increasing liquefied gas storage in Iraq, by a survey-type descriptive method and an applied purpose in 2023. The statistical population of the research consisted of all the senior managers, middle managers and officials of 15 oil and gas companies in Iraq 255 people, from which 154 people were selected to participate in the research using the Cochran formula and based on the stratified sampling method proportional to the volume. The data collection method is the library and field method. The tool for collecting data is a researcher-made questionnaire with 9 components (exploration stage risk, evaluation stage risk, development stage risk, gas condensate storage tank risk, ground surface facility risk, economic risk, technological risk, operational risk, legal and contractual risk) and 60 indicators, which were designed based on a 5-point Likert scale (very much, much, to some extent, little, very little). The validity was confirmed based on face, content and construct validity in Smart PLS software. The reliability coefficient was estimated using Cronbach’s alpha as 0.9. Further, SPSS software was used in two descriptive and inferential levels in order to analyze the data. The findings indicated that risk management in the oil and gas industry of Iraq is above average in order to increase liquefied gas storage in Iraq. In addition, exploration stage risk with a mean rank of (6.07) ranked 1st among the components of risk management, evaluation stage risk with a mean rank of (5.55) ranked 2nd, development stage risk with a mean rank of (5.09) ranked 3rd, ground level facility risk with a mean rank of (5.03) ranked 4th, operational risk with a mean rank of (4.93) ranked 5th, economic risk with a mean rank of (4.81) ranked 6th, the risk of gas condensate storage tanks with a mean rank of (4.66) ranked 7th, legal and contractual risk with a mean rank of (4.48) ranked 8th, technological risk with a mean rank of (4.37) ranked 9th.